Knowledge Test for Rainfed Farmers on Natural Resource Management Practices (Indian Journal of Extension Education, 2022)
Natural resource management (NRM) aims on efficient and sustainable utilization of natural resources. One of the greatest challenges facing the world is meeting the rising demand for food with a sustainable natural resource base. Agriculture, a sector being dependent on natural resources, it is high time to make farmers aware on the importance of NRM which require measuring the knowledge level of farmers on NRM practices for the better dissemination of NRM technologies. The study attempted to construct a knowledge test to measure the knowledge level of rainfed farmers during 2021. Items about NRM were collected from relevant literature and through consultation with experts. One pilot study was conducted in Lingaipalle village of Mahabubnagar district of Telangana for item analysis during September 2021. Item analysis provided item difficulty index, item discrimination index and item validity index. Based on the criteria, a total of 18 items were selected in the final test. To administer the knowledge test, one mark for each correct answer and zero mark for each wrong answer was assigned. Finally, the reliability of the test using split-half method found to be 0.749 indicating that the knowledge test is highly reliable for the present study.